Homoharringtonine stabilizes secondary structure of guanine-rich sequence existing in the 5′-untranslated region of Nrf2. Issue 16 (15th August 2019) - Kang, Jong-Su; Lee, June; Nam, Le Ba; Yoo, Ok-Kyung; Pham, Kim-Thanh; Duong, Thi-Hoai-Men; Keum, Young-Sam
Graphical abstract: Abstract: Homoharringtonine, known as omacetaxine mepesuccinate, is a pharmaceutical drug substance approved for treatment of chronic myeloid leukemia. Here, we report that homoharringtonine (HHT) is a novel chemical inhibitor of NRF2. HHT significantly suppressed NRF2 and ARE-dependent gene expression in human lung carcinoma A549 cells. HHT stabilized secondary structure of guanine-rich sequence existing in the 5′-untranslated region (5′-UTR) of Nrf2 and sensitized A549 cells to etoposide-induced apoptosis. To the best of our knowledge, HHT is the first type of transcriptional inhibitor of Nrf2 that stabilizes guanine-rich sequence existing in the 5′-UTR. Our study also provides a novel mechanism of action underlying how HHT exerts anti-carcinogenic effects in cancer cells.